2020
DOI: 10.37290/ctnr2641-452x.19:146-156
|View full text |Cite
|
Sign up to set email alerts
|

Herbs for Treatment of Hyperlipidemia: What is the Evidence?

Abstract: Hyperlipidemia is currently listed as one of the leading problems associated with the increased risk of coronary and extra-coronary atherosclerosis and cardiovascular diseases worldwide. Since the effectiveness of the existing medications differ, the potential use of herbs and their effects on the hyperlipidemia is of great interest. This review summarizes observations on the efficacy of plant bioactive compounds in the management of hyperlipidemia. Based on the available randomized controlled clinical trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study investigated the effects of MLE on BW, the level of blood lipid level, liver tissue morphology and liver function parameters in HFDinduced hyperlipidaemia rats. Body weight affects the onset and management of hyperlipidaemia [3] . It has been clearly shown that HFD induced hyperlipidaemia rats was proved to be a useful model for the development of CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigated the effects of MLE on BW, the level of blood lipid level, liver tissue morphology and liver function parameters in HFDinduced hyperlipidaemia rats. Body weight affects the onset and management of hyperlipidaemia [3] . It has been clearly shown that HFD induced hyperlipidaemia rats was proved to be a useful model for the development of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the development and complications of this disease induced by consuming long-term HFD is direct related to a series of inflammation and lipid accumulation that affect and impair the disorder of lipid metabolism. Several laboratory studies point to the health-promoting effects of various active chemical ingredients from traditional herbal origin without side effects that are able to regulating the gene and protein expression levels linked to hyperlipidaemia [3] . Considering the effectiveness of the existing medications differ, the use of natural medicine for improving hyperlipidaemia would be of tremendous benefit [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, Olea europea has some serious preventative value when it comes to metabolic illnesses and their consequences. Well-specified phenolic compounds and their doses, from a well-established source, in the formulation that would offer their highest bioavailability are needed for developing more reliable multicenter, placebo-controlled, randomized trials on hyperlipidemia patients 80,81 .…”
Section: Olive (Olea Europea)mentioning
confidence: 99%